Open Common Bile Duct Exploration in a Nigerian Tertiary Hospital - Adewale Adisa; Olusegun Alatise; Olalekan Olasehinde; Bolanle Ibitoye; Olukayode Arowolo,; Oladejo Lawal (The Annals of African Surgery, 2018)
Background: The prevalence of extra-hepatic biliary stones in Nigeria is unknown and its treatment frequently undocumented. We have observed an increase in bile duct exploration in our hospital. Methods: This is an eight-year retrospective report on consecutive patients who underwent common bile duct exploration. The diagnosis, pre-operative preparation, intra-operative findings and post-operative outcome were documented. Results: Forty-one patients were explored; 33 females (80.5%) and 8 (19.5%) males. Four had sickle cell anaemia. Pre-operative ultrasound showed common duct dilatation in 36 (87.8%), and choledocholithiasis in 29 (70.7%). Six patients did abdominal CT, 2 MRCP and none ERCP. Choledocholithiasis was operatively confirmed in 39 (95.1%) and dilated CBD without stones in 2. T-tube was inserted in 17 (41.5%) and primary closure of the common duct was done in 24 (58.5%). The mean duration of operation (102 vs 184 minutes) and hospital stay (10.6 vs 14.4 days) were less with primary closure. Conclusion: Common bile duct exploration is increasingly being performed in our center with a good outcome. There is increasing adoption of primary closure of the common bile duct in our setting.